High persister cell formation by clinical Staphylococcus aureus strains belonging to clonal complex 30. Issue 7 (19th July 2020) - Liu, Liping; Wang, Ying; Bojer, Martin Saxtorph; Andersen, Paal Skytt; Ingmer, Hanne
Abstract : Bacterial persisters form a subpopulation of cells that survive lethal concentrations of antibiotics without being genetically different from the susceptible population. They are generally considered to be phenotypic variants that spontaneously have entered a dormant state with low ATP levels or reduced membrane potential. In Staphylococcus aureus, a serious opportunistic human pathogen, persisters are believed to contribute to chronic infections that are a major global healthcare problem. While S. aureus persisters have mostly been studied in laboratory strains, we have here investigated the ability of clinical strains to form persisters. For 44 clinical strains belonging to the major clonal complexes CC5, CC8, CC30 or CC45, we examined persister cell formation in stationary phase when exposed to 100 times the MIC of ciprofloxacin, an antibiotic that targets DNA replication. We find that while all strains are able to form persisters, those belonging to CC30 displayed on average 100-fold higher persister cell frequencies when compared to strains of other CCs. Importantly, there was no correlation between persister formation and the cellular ATP content of the individual strains, but the group of CC30 strains displayed slightly lower membrane potential compared to the non-CC30 group. CC30 strains have previously been associated with chronic and reoccuring infections and we hypothesize that there could be a correlation between lineage-specific characteristics displayed via in vitro persister assays and the observed clinical spectrum of disease.